The role of the Virtual School in supporting improved educational outcomes for children in care. (4th July 2019) - Sebba, Judy; Berridge, David
ABSTRACT: In England, 'Virtual Schools' oversee and support the educational progress of children in care. This paper reports on the analysis of 16 interviews with Virtual School headteachers that were part of two mixed methods research projects on the educational progress of children in care. These interviews explored their role; the types of support they offer young people in care; what they see as the key factors about a young person's individual characteristics and care experiences that influence their educational outcomes; how schools support young people in care; and the influence of the foster carer/residential staff on the educational outcomes of these children. The interviews were analysed using NVivo and emerging themes were identified informed by the literature on the education of children in care. The paper draws out the main findings which explore the status and role of Virtual Schools in England, their functions, strategies, and what they see as their contribution to improving the educational outcomes of children in care.